Ideological-Aesthetic Significance of Stropha in the Poetry of the Independence Period - Oripova Gulnozakhan Murodilovna (Universitas Muhammadiyah Sidoarjo, 2024)
This study delves into the exploration of ideological-aesthetic and artistic poignancy within independence-era poetry through an analysis of strophic structures. Employing psychological, structural-poetic, and descriptive techniques, the research examines both the internal and external compositional properties of strophes. By focusing on the poetry of notable figures such as Sirozhiddin Sayyid, Fakhriyor, Abdulla Qutbiddin, Abdullah Sher, and Ulugbek Hamdam, various strophic structures are identified and analyzed. The conclusions drawn from this scientific inquiry serve as the foundation for advancing the scientific-theoretical understanding of lyrical genres in poetry, contributing valuable insights to the broader scholarly discourse. Highlights: The study investigates the intricate strophic structures of independence-era poetry, shedding light on their ideological-aesthetic significance. Psychological, structural-poetic, and descriptive techniques are utilized to dissect both internal and external compositional properties of strophes. By analyzing works of prominent poets like Sirozhiddin Sayyid and Abdullah Sher, the research contributes to a deeper understanding of lyrical genres and their artistic implications in poetry. Keywords: Strofa, Ideological-Aesthetic Property, Rhythm, Poetic Thought, Artistic Detail.